Iliac Conduits for Endovascular Treatment of Aortic Pathologies: A Systematic Review and Meta-analysis - Giannopoulos, Stefanos; Malgor, Rafael D.; Sobreira, Marcone L. [UNESP]; Siada, Sammy S.; Rodrigues, Diego; Al-Musawi, Mohammed; Malgor, Emily A.; Jacobs, Donald L. (Sage Publications Inc, 2021)
Purpose: The treatment of thoracoabdominal aortic aneurysm has largely shifted to endovascular techniques. However, severe iliofemoral arterial disease often presents a challenge during these interventions. As a result, iliac conduits have been introduced to facilitate aortic endovascular therapy. The goal of the current study was to gauge utilization and to analyze iliac artery conduit outcomes to facilitate endovascular therapy to treat aortic pathologies. Materials and Methods: A meta-analysis of 14 studies was conducted with the use of random effects modeling. The incidence of periprocedural adverse events was gauged based on iliac conduit vs nonconduit cases and planned vs unplanned iliac conduit placement. Outcomes of interest included length of hospital stay, morbidity and mortality associated to conduits, and all-cause mortality. Results: Iliac conduits, either open or endo-conduits, were utilized in 17% (95% CI: 9%-27%) of 16,855 cases, with technical successful rate of 94% (95% CI: 80%-100%). Periprocedural complications occurred in 32% (95% CI: 22%-42%) of the cases, with overall bleeding complication rate being 10% (95% CI: 5%-16%). Female patients, positive history for smoking, pulmonary disease, and peripheral artery disease at baseline were associated with more frequent utilization of iliac conduits. Conduit use was associated with longer hospitalization, higher periprocedural all-cause mortality (OR: 2.85; 95% CI: 1.75-4.64; p<0.001), and bleeding complication rate (OR: 2.38; 95% CI: 1.58-3.58; p<0.001). Sensitivity analysis among conduit cases showed that planned conduits were associated with fewer periprocedural complications compared to unplanned conduits (OR: 0.38; 95% CI: 0.20-0.73; p=0.004). Conclusion: Iliac conduit placement is a feasible strategy, associated with high technical success to facilitate complex aortic endovascular repair. However, periprocedural adverse event rate, including bleeding complications is not negligible. All-cause mortality and morbidity rates among cases that require iliac conduits should be strongly considered during clinical decision making. High-quality comparative analyses between iliac conduit vs nonconduit cases and between several types of iliac conduit grafts aiming at facilitating endovascular aortic repair are still needed to determine the best strategy to address challenging iliac artery accesses.
Keywords: EVAR; TEVAR; AAA; iliac conduit; endo-conduit; covered stent; endovascular treatment; therapy; EVT